Identifying key wine product and wine tourism attributes in an ultra-peripheral wine region: Implications for wine consumers and wine tourism - Kok, Seng Kiat; Duarte Alonso, Abel (Taylor & Francis (Routledge), 2020)
This study contributes to the wine marketing and wine tourism literature, and examines the preferences and experiences of consumers of local wines and winery visitation in the ultra-peripheral wine region of La Palma Island, Spain. An online survey administered among consumers of local wines resulted in 102 usable responses. Apart from highlighting wine preferences, with aroma, taste, originality and uniqueness standing out, the findings underscore the potential for wine education and wine tourism to contribute considerably to further marketing and positioning of an ultra-peripheral wine region. Indeed, participants predominantly indicated purchasing wines at supermarkets and consuming wines at their home-accommodation, illustrating the opportunities for wineries to enhance knowledge, travel experiences, and ultimately consumption and appreciation. The study has important implications, including approaches for ultra-peripheral regions to develop wine and wine tourism offerings, as well as to position themselves, through maximising the distinctness of their wine heritage, core products, and experiences.